Solid modeler evaluation and comparison: perspective of computer science - Romli, Awanis; Haron, Habibollah (Penerbit UTM Press, 2007)
Solid modeling theory and technology are maturing rapidly. We have seen explosive growth in the field based on scientific literature reviews, and by the number of solid modelers that are commercially available. Constructive Solid Geometry (CSG) is a method used to represent solid objects in many contemporary solid modeling systems. A CSG representation is a binary tree whose nonterminal nodes represent Boolean operations and whose terminal nodes represent primitive solids. In this paper, the comparison between four solid modelers in term of their difficulties and friendliness in designing and representing a solid object are presented. The solid modelers are AutoCAD 2004, Solid Edge V12, SolidWorks 2001 plus, and 3D Studio Max 7. The research methodology is based on Solid Modeler Evaluation and Comparison Cycle (SMECC) methodology. This paper documents seven performance parameters in the design process namely, extrusion, setup time, ease of use, speed, flexibility, feature based design, and CSG tree. The outcomes presented by this paper is expected to assist companies and design educators in making solid modeler selection decisions